Positive electrode mixture and lithium secondary battery

By using lithium transition metal oxide, polyvinylidene fluoride and carbon nanotubes in the positive electrode composite of lithium secondary batteries, the amount of lithium hydroxide is controlled between 0.15% and 0.35%, which solves the problem of reducing discharge rate characteristics caused by thick positive electrode composite layer, and achieves higher ion diffusion and discharge performance.

CN119601650APending Publication Date: 2025-03-11TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410817216.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-11
Filing Date
2024-06-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When forming a relatively thick positive electrode composite layer, the adhesive and conductive additive may float to the surface, resulting in a decrease in ion diffusion, which in turn affects the discharge rate characteristics of the lithium secondary battery.

Method used

A positive electrode composite composed of lithium transition metal oxide, polyvinylidene fluoride and carbon nanotubes is used to ensure that the amount of lithium hydroxide is between 0.15% and 0.35% to inhibit the migration of binder and conductive additives.

Benefits of technology

The reduction in the discharge rate characteristics of the lithium secondary battery of the thick positive electrode composite layer is effectively suppressed, and the ion diffusion and discharge performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601650A_ABST
    Figure CN119601650A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode mixture and a lithium secondary battery. The positive electrode mixture contains: a positive electrode active material comprising a lithium transition metal oxide having a layered crystal structure; a binder; and a conductive auxiliary agent. The lithium transition metal oxide includes nickel, cobalt, and manganese. And the binder comprises polyvinylidene fluoride. The conductive auxiliary agent comprises a carbon nano tube. The amount of lithium hydroxide contained in the positive electrode active material is 0.15% by mass or more and 0.35% by mass or less relative to the total amount of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode composite material and a lithium secondary battery. Background Art

[0002] Lithium secondary batteries using non-aqueous electrolytes (hereinafter also referred to as "lithium secondary batteries") have been used in information and communication technologies (for example, personal computers, smartphones, etc.), vehicles, power storage, and the like.

[0003] Japanese Patent Publication No. 2019-164960 discloses a method for manufacturing a positive electrode for a non-aqueous electrolyte lithium secondary battery. The manufacturing method comprises: a process of preparing a positive electrode composite paste using a positive electrode active material, polyvinylidene fluoride, acetic anhydride and a solvent; a process of coating the positive electrode composite paste on a positive electrode collector; and a process of drying the coated positive electrode composite paste. The mass ratio of LiOH contained in the positive electrode active material to the polyvinylidene fluoride is greater than 0.040 and less than 0.075. The amount of acetic anhydride is greater than 0.01% by mass and less than 0.2% by mass relative to the amount of all solid components when preparing the positive electrode composite paste. Summary of the invention

[0004] When forming a relatively thick positive electrode composite layer (weight per unit area of ​​38mg / cm 2 In the case of a positive electrode composite layer (above), migration may occur. The so-called "migration" refers to the phenomenon that the binder (such as polyvinylidene fluoride, etc.) and the conductive aid float to the surface of the coating when the positive electrode composite paste is dried. If migration occurs, the ion diffusion of the resulting positive electrode composite layer may be reduced. As a result, the discharge rate characteristics of the lithium secondary battery may be reduced.

[0005] The present disclosure is completed in view of the above-mentioned actual situation.

[0006] An object of one embodiment of the present disclosure is to provide a positive electrode mixture and a lithium secondary battery capable of suppressing a decrease in discharge rate characteristics of a lithium secondary battery having a relatively thick positive electrode mixture layer.

[0007] Means for solving the above-mentioned problems include the following embodiments.

[0008] 1. A positive electrode composite material comprising: a positive electrode active material composed of a lithium transition metal oxide having a layered crystal structure, a binder and a conductive aid, wherein the lithium transition metal oxide contains nickel, cobalt and manganese, the binder contains polyvinylidene fluoride, the conductive aid contains carbon nanotubes, and the amount of lithium hydroxide contained in the positive electrode active material is greater than 0.15% by mass and less than 0.35% by mass relative to the total amount of the positive electrode active material.

[0009] 2. A lithium secondary battery comprising: a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, wherein the positive electrode has a positive electrode composite layer comprising the positive electrode composite described in 1 above.

[0010] 3. The lithium secondary battery according to 2 above, wherein the mass per unit area of ​​the positive electrode composite layer is 35 mg / cm 2 Up to 46mg / cm 2 .

[0011] 4. The lithium secondary battery according to 3 above, wherein the mass per unit area of ​​the positive electrode composite layer is 35 mg / cm 2 Up to 40mg / cm 2 .

[0012] According to the present disclosure, a positive electrode mixture and a lithium secondary battery are provided, which are capable of suppressing a decrease in the discharge rate characteristics of a lithium secondary battery having a relatively thick positive electrode mixture layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:

[0014] Figure 1 A graph showing the zeta potential difference ΔV with respect to the amount of LiOH contained in the positive electrode active material in Reference Examples 1 to 14;

[0015] Figure 2 A graph showing 1C discharge rate relative to the amount of lithium hydroxide contained in the positive electrode active material of Examples 1 to 9 and Comparative Examples 1 to 4; and

[0016] Figure 3 It is a graph showing the 1C discharge rate with respect to the drying temperature of the coating film of the positive electrode composite paste. DETAILED DESCRIPTION

[0017] In the present disclosure, the numerical ranges specified by "AB", "A to B", "from A to B", etc. represent the range including the minimum value A and the maximum value B. In the numerical ranges recorded in stages in the present disclosure, the upper limit value or the lower limit value recorded in a certain numerical range can be replaced by the upper limit value or the lower limit value of another numerical range recorded in stages. In the numerical ranges recorded in the present disclosure, the upper limit value or the lower limit value recorded in a certain numerical range can be replaced by the values ​​shown in the embodiments. In the present disclosure, the combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, the amount of each component, when there are multiple substances equivalent to the component, refers to the total amount of the multiple substances unless otherwise specified. In the present disclosure, the term "process" is not only an independent process, but also is included in this term as long as the expected purpose of the process is achieved even if it cannot be clearly distinguished from other processes.

[0018] (1) Positive electrode composite material

[0019] The positive electrode composite material disclosed herein contains a positive electrode active material composed of a lithium transition metal oxide having a layered crystal structure, a binder and a conductive aid. The lithium transition metal oxide contains nickel (Ni), cobalt (Co) and manganese (Mn). The binder contains polyvinylidene fluoride (hereinafter also referred to as "PVDF"). The conductive aid contains carbon nanotubes (hereinafter also referred to as "CNT"). The amount of lithium hydroxide contained in the positive electrode active material (hereinafter also referred to as "LiOH amount") is 0.15% by mass or more and 0.35% by mass or less relative to the total amount of the positive electrode active material.

[0020] In the present disclosure, the term "positive electrode composite material" refers to the solid content of the positive electrode composite layer contained in the positive electrode of a lithium secondary battery. A lithium secondary battery may be a battery containing a solid electrolyte or a battery containing a non-aqueous electrolyte.

[0021] The so-called "lithium transition metal oxide" refers to a compound that can reversibly occlude and release lithium ions and contains LiOH. The lithium transition metal oxide can be represented by LiMO2. M contains Ni, Co and Mn, and may further contain at least one selected from V, Cr, Fe, Cu, Zr, Nb, Mo, Ru, Pd, Ag, Hf, Ta, W, Ir, Pt, Au and Pb.

[0022] The “layered crystal structure of a lithium transition metal oxide” refers to a crystal structure in which lithium layers and transition metal layers containing nickel, cobalt, and manganese are alternately arranged.

[0023] The so-called "positive electrode active material" refers to a powder having lithium transition metal oxide particles (hereinafter also referred to as "positive electrode active material particles") as the main component. The so-called "main component" means that the proportion of lithium transition metal oxide particles relative to the total amount of positive electrode active material is 50% by mass or more. The proportion of lithium transition metal oxide particles relative to the total amount of positive electrode active material can be 100% by mass.

[0024] The positive electrode composite material disclosed in the present invention has the above-mentioned structure, so it is possible to suppress the formation of a relatively thick positive electrode composite material layer (for example, a unit area mass of 38 mg / cm 2 The discharge rate characteristics of the lithium secondary battery having the positive electrode composite layer or the like are reduced.

[0025] This effect is presumably due to the following reasons, but the present invention is not limited thereto.

[0026] In the present disclosure, the amount of LiOH is greater than 0.15 mass % and less than 0.35 mass %. Thus, when a relatively thick coating of a positive electrode composite paste containing the positive electrode composite of the present disclosure is dried, PVDF easily adheres to the surface of the particles of the positive electrode active material. CNT has a high affinity for PVDF. CNT easily adheres to PVDF attached to the positive electrode active material particles. Therefore, migration is difficult to occur. As a result, it is speculated that the positive electrode composite of the present disclosure can suppress the reduction in the discharge rate characteristics of a lithium secondary battery having a relatively thick positive electrode composite layer.

[0027] (1.1) Positive electrode active material

[0028] The positive electrode active material is composed of a lithium transition metal oxide. The lithium transition metal oxide contains nickel, cobalt and manganese and can be represented by the following formula (I).

[0029] Formula (I): LiNi x Co y Mn z O2

[0030] In formula (I), the relationship of 0.5≤x<1, 0<y, 0<z, and x+y+z=1 is satisfied. x may be 0.60 or more, 0.80 or more, or 0.90 or more.

[0031] The positive electrode active material may be composed of one lithium transition metal oxide or may be composed of at least two lithium transition metal oxides.

[0032] The amount of LiOH contained in the positive electrode active material is 0.15 mass % to 0.35 mass % relative to the total amount of the positive electrode active material. The amount of LiOH contained in the positive electrode active material may be 0.19 mass % to 0.35 mass %, 0.23 mass % to 0.35 mass %, or 0.31 mass % to 0.35 mass % relative to the total amount of the positive electrode active material. The method for determining the amount of LiOH is the same as that described in the embodiment.

[0033] The average particle size of the positive electrode active material may be 1 μm to 20 μm, and may be 5 μm to 15 μm. The “average particle size” refers to the particle size (median diameter) corresponding to 50% by volume of the cumulative frequency from the side of the particles with a small particle size in the volume-based particle size distribution based on the laser diffraction and light scattering method.

[0034] The content of the positive electrode active material may be greater than 50% by mass, or may be 80% by mass or more and 97% by mass or less, relative to the total amount of the positive electrode composite material.

[0035] (1.2) Binder

[0036] The binder includes PVDF and may also include other binders different from PVDF. The binder may be PVDF. As other binders, for example, carboxymethyl cellulose, rubber-based binders, fluoride-based binders, polyolefin-based thermoplastic resins, imide-based resins, amide-based resins, acrylic resins, methacrylic resins, etc. Rubber-based binders are, for example, butadiene rubber, hydrogenated butadiene rubber, etc. Fluoride-based binders are, for example, polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), etc. Polyolefin-based thermoplastic resins are, for example, polyethylene, polypropylene, polystyrene, etc. Imide-based resins are, for example, polyimide, polyamide-imide, etc. Amide-based resins are, for example, polyamide, etc. Acrylic resins are, for example, polymethyl acrylate, polyethyl acrylate, etc. Methacrylic resins are, for example, polymethyl methacrylate, polyethyl methacrylate, etc.

[0037] The content of the binder may be 0.1 mass % to 10 mass % relative to the total amount of the positive electrode composite material.

[0038] (1.3) Conductive additives

[0039] The conductive aid includes CNT and may also include a carbon material. The conductive aid may be CNT. CNT has a cylindrical shape in which a graphene sheet is wound into a single layer or multiple layers. CNT includes at least one of a single-layer carbon nanotube and a multi-layer carbon nanotube (hereinafter also referred to as "MWCNT"). Examples of carbon materials include carbon black (e.g., acetylene black, furnace black, Ketjen black, etc.), coke, graphite, etc.

[0040] The content of the conductive additive may be 0.1 mass % to 10 mass % relative to the total amount of the positive electrode composite.

[0041] (2) Lithium secondary battery

[0042] The lithium secondary battery disclosed in the present invention comprises: a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and a non-aqueous electrolyte. The positive electrode has a positive electrode composite material layer containing the positive electrode composite material disclosed in the present invention. Thus, even if the thickness of the positive electrode composite material layer of the lithium secondary battery disclosed in the present invention is relatively thick, the reduction of the discharge rate characteristics can be suppressed.

[0043] The structure of the lithium secondary battery is not particularly limited, and examples thereof include a winding type and a stacked type. The winding type is formed by winding a ruler-shaped (long ruler-shaped) electrode body in which a negative electrode, a separator and a positive electrode are stacked in sequence. The stacked type is formed by stacking a single-page (printing paper-shaped) electrode body in which a negative electrode, a separator and a positive electrode are stacked in sequence.

[0044] (2.1) Positive electrode

[0045] The positive electrode has a positive electrode composite layer and may further have a positive electrode current collector (such as aluminum foil). The positive electrode composite layer is laminated on at least one main surface of the positive electrode current collector. The positive electrode composite layer includes the positive electrode composite of the present disclosure.

[0046] The mass per unit area of ​​the positive electrode composite layer is preferably 35 mg / cm 2 Up to 46mg / cm 2 As a result, the reduction in the discharge rate characteristics of the lithium secondary battery is further suppressed.

[0047] The mass per unit area of ​​the positive electrode composite layer is more preferably 35 mg / cm 2 Up to 40mg / cm 2 As a result, the reduction in the discharge rate characteristics of the lithium secondary battery is further suppressed.

[0048] (2.2) Negative electrode

[0049] The negative electrode has a negative electrode current collector, and may or may not further have a negative electrode mixed material layer.

[0050] In the case where the negative electrode does not have a negative electrode composite layer, the negative electrode current collector includes a main surface where lithium metal is precipitated during charging. Specifically, the lithium ions contained in the non-aqueous electrolyte accept electrons on the negative electrode current collector by charging, and lithium metal is precipitated. The precipitated lithium metal dissolves as lithium ions in the non-aqueous electrolyte by discharging. The lithium ions contained in the non-aqueous electrolyte may be at least one of ions from a lithium salt described later and ions supplied from a positive electrode active material by charging.

[0051] In the case where the negative electrode has a negative electrode composite layer, the negative electrode composite layer is stacked on at least one main surface of the negative electrode collector (such as copper foil, etc.). The negative electrode composite layer contains a negative electrode layer active material that can absorb and release charge carriers (such as carbon (such as natural graphite, artificial graphite), a compound that can be alloyed with lithium (such as silicon, tin, etc.)). The negative electrode composite layer may further contain a conductive aid for improving electronic conductivity, a binder, an electrolyte supporting salt (lithium salt) for improving ion conductivity, a polymer electrolyte, and an additive as needed. Conductive aids are, for example, acetylene black, etc. Binders are, for example, polyvinylidene fluoride, etc. Additives are, for example, trifluoropropylene carbonate, etc. The negative electrode can be a known structure.

[0052] (2.3) Separator

[0053] The separator keeps the positive electrode and the negative electrode spaced apart to prevent contact short circuits from occurring, while allowing lithium ions to pass through. Examples of separators include porous resin sheets or nonwoven fabrics. Examples of materials for the porous resin sheets include polyolefins (polypropylene, polyethylene, etc.). Examples of materials for the nonwoven fabrics include polypropylene, polyethylene terephthalate, methylcellulose, etc. The separator may be a known structure.

[0054] (2.4) Non-aqueous electrolyte

[0055] The non-aqueous electrolyte may include a non-aqueous solvent and a lithium salt. Examples of lithium salts include LiClO4, LiAsF6, LiPF6, LiBF4, LiCF3SO3, LiN(FSO2)2, and LiN(CF3SO2)2. Examples of non-aqueous solvents include cyclic carbonates, chain carbonates, cyclic esters, chain esters, and ethers. Examples of cyclic carbonates include ethylene carbonate, etc. Examples of chain carbonates include dimethyl carbonate and ethyl methyl carbonate, etc. Examples of cyclic esters include γ-butyrolactone and γ-valerolactone, etc. Examples of chain esters include methyl formate and methyl acetate, etc. Examples of ethers include dimethoxyethane and ethoxymethoxyethane, etc. The non-aqueous electrolyte may include additives (e.g., vinylene carbonate, lithium bis(oxalate)borate, etc.) and the like.

[0056] (2.5) Housing

[0057] A lithium secondary battery generally has a housing. The housing accommodates a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. The housing is not particularly limited, and examples thereof include laminated films (e.g., aluminum sheets), battery cans (e.g., cylindrical, square, coin-shaped, etc.), and the like.

[0058] The present disclosure will be described in more detail below using examples, but the present invention is not limited to these examples.

[0059] [1] Calculation of the amount of LiOH in the positive electrode active material

[0060] The amount of LiOH in the positive electrode active material was calculated using the neutralization titration method. Specifically, 100 mL of pure water was added to 10 g of the positive electrode active material and stirred for 1 minute to obtain a dispersion. The dispersion was filtered by suction to obtain a filtrate. 25 μL of hydrochloric acid was dripped into the filtrate every 30 seconds for titration. The OH in lithium hydroxide (LiOH) was calculated using the neutralization titration method. - The amount of OH - With lithium ion (Li + ) molar ratio (OH - mol / Li + The molar ratio of OH is 1 / 1. - Calculate the amount of Li + The amount of lithium from LiOH. - The amount and Li + The mass of LiOH is calculated from the amount of LiOH in the positive electrode active material. The ratio of the mass of LiOH to the total amount of the positive electrode active material (ie, the "amount of LiOH") is calculated.

[0061] When the positive electrode active material is composed of one type (positive electrode active material A), the amount of LiOH in the positive electrode active material A is referred to as “the amount of LiOH in the positive electrode active material”.

[0062] When the positive electrode active material is composed of two kinds (positive electrode active material A and positive electrode active material B), the calculated value of the following formula (1) is set as the "LiOH amount of the positive electrode active material". In formula (1), the "mixing ratio of positive electrode active material A" refers to the ratio of the mass of positive electrode active material A relative to the total amount of positive electrode active material. The "mixing ratio of positive electrode active material B" refers to the ratio of the mass of positive electrode active material B relative to the total amount of positive electrode active material.

[0063] Formula (1): LiOH amount of positive electrode active material = LiOH amount of positive electrode active material A × mixing ratio of positive electrode active material A + LiOH amount of positive electrode active material B × mixing ratio of positive electrode active material B

[0064] [2] Relationship between the amount of LiOH in the positive electrode active material and the zeta potential

[0065] The positive electrode active material shown in Table 1 was prepared. The positive electrode active material and N-methylpyrrolidone (NMP) (solvent for the positive electrode composite paste) were mixed to obtain a first solution. The solid content concentration NV (NonVolatile) of the positive electrode active material in the first solution was 75% by mass. The positive electrode active material, polyvinylidene fluoride (PVDF) (binder for the positive electrode composite paste) and N-methylpyrrolidone (NMP) (solvent for the positive electrode composite paste) were mixed to obtain a second solution. The solid content concentration NV (NonVolatile) of the positive electrode active material in the second solution was 75% by mass. The content of PVDF was 1.4% by mass relative to the total of 100% by mass of the positive electrode active material and PVDF. The zeta potential V1 of the first solution and the zeta potential V2 of the second solution were measured by ultrasonic attenuation method. The zeta potential difference ΔV (mV) (absolute value) was calculated according to the following formula (2). The calculation results are shown in Figure 1 and Table 1.

[0066] Formula (2): zeta potential difference ΔV (mV) = |zeta potential V1 of the first solution - zeta potential V2 of the second solution |

[0067] Table 1

[0068]

[0069] "Single particle" refers to a particle having the continuity of one crystal (one crystal) (i.e., "primary particle"). "Polycrystalline" refers to a particle not having the continuity of one crystal (one crystal). Specifically, "polycrystalline" refers to a secondary particle formed by sintering primary particles.

[0070] As shown in Table 1, it can be seen that the higher the amount of LiOH in the positive electrode active material, the smaller the zeta potential difference ΔV tends to be. PVDF has fluorine atoms (F) with large electronegativity. Therefore, if PVDF is adsorbed on the surface of the particles of the positive electrode active material, the repulsion between the particles of the positive electrode active material becomes larger, and the zeta potential of the second solution becomes larger. If PVDF is not attached to the positive electrode active material and exists alone, the repulsion between the particles of the positive electrode active material is small. Therefore, if the amount of LiOH is large, PVDF is difficult to attach to the surface of the active material, so the zeta potential difference is small. As a result, migration is likely to occur. CNT has a high affinity for PVDF. Therefore, if PVDF is present on the surface of the particles of the positive electrode active material, CNT is also easy to attach to the surface of the particles of the positive electrode active material.

[0071] As for the amount of LiOH in the positive electrode active material, as shown in Table 1, generally, the higher the Ni ratio of the active material, the higher the LiOH amount of the positive electrode active material tends to be. Due to the different synthesis methods of the positive electrode active material, the positive electrode active material is generally roughly divided into a powder with a high content of primary particles (single particle type) and a powder with a high content of secondary particles (polymorphic). When the positive electrode active material is polymorphic, the amount of LiOH in the positive electrode active material tends to be high. If the Ni ratio of the positive electrode active material is high and the positive electrode active material is polymorphic, the amount of LiOH in the positive electrode active material tends to increase. If the amount of LiOH in the positive electrode active material is too high (the amount of LiOH exceeds 0.35%), it becomes difficult for PVDF to adhere to the surface of the particles of the positive electrode active material. As a result, migration is likely to occur. If LiOH is present in large quantities on the surface of the particles of the positive electrode active material, it is difficult for PVDF to adhere to the surface of the particles of the positive electrode active material.

[0072] [3] Examples and Comparative Examples

[0073] [3.1] Examples 1 to 7 and Comparative Examples 1 to 4

[0074] Positive electrode active materials A and B shown in Table 2 were prepared. The compositions of the positive electrode active materials A and B were LiNi x Co y Mn z O2 (0.60≤x<1, 0<y, 0<z, x+y+z=1) As the positive electrode active material, a powder obtained by mixing the positive electrode active material A and the positive electrode active material B at the ratio shown in Table 2 was prepared.

[0075] The positive electrode composite paste was prepared by mixing the positive electrode active material shown in Table 2, carbon nanotubes (MWCNT) as a conductive aid, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a solvent. The mass ratio of the positive electrode active material, MWCNT, and PVDF (positive electrode active material: MWCNT: PVDF) is 97.8:0.7:1.4. The positive electrode composite paste was applied to an aluminum foil (thickness: 30 μm) using a scraper to form a coating. The coating was dried at 90°C to 125°C for 30 minutes. The dried coating was pressed with a roller press so that the electrode density became 3.2 g / cc. Thus, a positive electrode was obtained.

[0076] As a separator, a three-layer porous resin sheet (thickness: 16 μm) was prepared. The porous resin sheet was formed by sequentially stacking a polypropylene (PP) layer, a polyethylene (PE) layer, and a PP layer. As a negative electrode, Li metal was prepared.

[0077] The positive electrode, separator and negative electrode are stacked in sequence and housed in a battery case with an injection port. A non-aqueous electrolyte is injected from the injection port of the battery case, and the injection port is sealed to produce a coin battery cell (lithium secondary battery). The non-aqueous electrolyte contains a mixed solvent, LiPF6 as a supporting salt, and vinylene carbonate (VC) as an additive. The mixed solvent contains ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). The volume ratio of EC to DMC and EMC (EC: DMC: EMC) is 30:40:30. LiPF6 is dissolved at a concentration of 1.1 mol / L. The content of VC is 1% by mass relative to the total amount of the non-aqueous electrolyte.

[0078] [3.2] Activation of lithium secondary batteries

[0079] The initial charging current was set to constant current-constant voltage mode. Constant current (CC) charging was performed with a current value of 0.1C until 4.25V, constant voltage charging was performed until the constant voltage charging time became 3 hours, and constant current mode was used to discharge with a current value of 0.1C until 2.5V to activate the lithium secondary battery.

[0080] [3.3] 1C discharge maintenance rate of lithium secondary batteries

[0081] The charge and discharge are set to constant current mode. The current rate is set to 0.1C or 1.0C. Specifically, in the above [2.2], the total discharge capacity when discharging from 4.25V to 2.5V with a current value of 0.1C (hereinafter also referred to as "0.1C-CC discharge capacity") is measured. Secondly, constant current (CC) charging is performed with a current value of 1C until 4.25V, constant voltage charging is performed until the constant voltage charging time becomes 3 hours, and constant current mode is used to discharge with a current value of 1C until 2.5V. The total discharge capacity at this time (hereinafter also referred to as "1C-CC discharge capacity") is measured. According to the following formula (3), the "1C discharge maintenance charge rate (%)" is calculated. The calculation results are shown in Figure 2 and Table 2. The permissible range of 1C discharge maintenance charge rate is above 73%.

[0082] Formula (3): 1C discharge maintenance charge rate (%) = (0.1C-CC discharge capacity / 1.0C-CC discharge capacity) × 100

[0083] [3.4] Results

[0084] Table 2

[0085]

[0086] Even if the amount of LiOH is higher than 0.35%, when the mass per unit area of ​​the positive electrode is small (for example, when the mass per unit area of ​​the positive electrode is less than 38 mg / cm2 In the case of ), the 1C discharge maintenance rate tends to be high. If the positive electrode unit area mass of the positive electrode increases (the thickness of the positive electrode becomes thicker), the ion diffusion in the positive electrode becomes the rate limit (the ion diffusion in the positive electrode becomes the limit). Therefore, the influence of migration becomes obvious, and the reduction in discharge rate tends to become larger.

[0087] [3.4.1] Comparative Examples 1 to 4

[0088] In Comparative Examples 1 to 4, the amount of LiOH in the positive electrode active material is not within the range of 0.15% to 0.35%. 2 These results show that the positive electrode composites of Comparative Examples 1 to 4 are not positive electrode composites that can suppress the reduction in discharge rate characteristics of lithium secondary batteries having relatively thick positive electrode composite layers.

[0089] [3.4.2] Example 1 to Example 7

[0090] In Examples 1 to 7, the amount of LiOH in the positive electrode active material is in the range of 0.15% to 0.35%. Therefore, when the positive electrode unit area mass is 38 mg / cm 2 From these results, it can be seen that the positive electrode composite materials of Examples 1 to 7 are positive electrode composite materials that can suppress the reduction in discharge rate characteristics of lithium secondary batteries having relatively thick positive electrode composite layers.

[0091] [3.5] Drying temperature of coating

[0092] It can be seen that by adjusting the amount of LiOH in the positive electrode active material within the range of 0.15% to 0.35%, migration is less likely to occur. Therefore, the drying temperature of the coating when making the positive electrode composite layer can be increased. For the configuration in which the amount of LiOH in the positive electrode active material is 0.35% and the configuration in which the amount of LiOH in the positive electrode active material is 0.37%, positive electrodes with different coating drying temperatures were made, and the 1C discharge maintenance rate was calculated. The results are shown in Figure 3 .

[0093] like Figure 3 As shown, when the amount of LiOH in the positive electrode active material is 0.35%, the 1C discharge maintenance rate is still high even if the drying temperature is increased. When the amount of LiOH in the positive electrode active material is 0.37%, the migration becomes larger by increasing the drying temperature, and the 1C discharge maintenance rate is low.

Claims

1. A positive electrode composite material comprising: a positive electrode active material composed of a lithium transition metal oxide having a layered crystal structure, a binder and a conductive additive, The lithium transition metal oxide comprises nickel, cobalt and manganese, the binder comprises polyvinylidene fluoride, and the conductive additive comprises carbon nanotubes. The amount of lithium hydroxide contained in the positive electrode active material is 0.15 mass % or more and 0.35 mass % or less relative to the total amount of the positive electrode active material.

2. A lithium secondary battery comprising: A positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, wherein the positive electrode has a positive electrode composite material layer containing the positive electrode composite material according to claim 1.

3. The lithium secondary battery according to claim 2, wherein: The unit area mass of the positive electrode composite layer is 35 mg / cm 2 ~46mg / cm 2 .

4. The lithium secondary battery according to claim 3, wherein: The unit area mass of the positive electrode composite layer is 35 mg / cm 2 ~40mg / cm 2 .

Citation Information

Patent Citations

  • Method for manufacturing positive electrode for nonaqueous electrolyte lithium secondary battery

    JP2019164960A